The Use Of Re-Infiltration For Management Of Open Pit Gold Mine Dewatering Discharge - M. Saunders Macdonald (Society for Mining, Metallurgy & Exploration, 1996)
A number of open pit gold mines in Nevada extract ore from areas below natural groundwater elevations, necessitating dewatering and some method of disposal of the extracted water. These open pits extend well below the water table, with associated dewatering volumes greater than 10,000 gpm. Some mines, with large volumes of dewatering water to manage, have constructed re-infiltration basins to re-introduce dewatering water to the groundwater system some distance from the pits. This paper presents an overview of the state of the art of re-infiltration projects, including the permit process for such projects in Nevada, and the necessary engineering considerations.